PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BHAKTI KARYA DISTRIBUSI INDONESIA - Suci Miramadanis, Pramutia; Yani Nasution, Ahmad (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the partial and simultaneous influence of leadership style and work environment on employee performance at PT. Bhakti Karya Distribution Indonesia. This type of research is a type of quantitative research using associative methods. The data collection technique uses a questionnaire method, the population in this study is all employees of PT. Bhakti Karya Distribution Indonesia, namely 59 employees. Sample of 59 employees. Data analysis uses descriptive analysis, data instrument test, classical assumption test, linear regression test, correlation coefficient test, coefficient of determination test, as well as t test and f test using SPSS version 26 tools. The results of this research are that Leadership Style has a significant effect on Performance Employees with a coefficient of determination value of 68.3% and hypothesis testing obtained t count > t table or (11,085 > 1,672). The work environment has a significant effect on employee performance with a coefficient of determination value of 56.3% and the hypothesis test obtained t count > t table or (8,574 > 1,672). Leadership Style and Work Environment simultaneously have a significant effect on Employee Performance with the regression equation Y = 4,202 + 599 X1 + 191 X2. The coefficient of determination value is 69.4% while the remaining 30.6% is influenced by other factors. The autocotellation test obtained was 0.833. The hypothesis test obtained a calculated f value > f table or (63,526 > 3,162).